Eketankire or hidden time in the calendars of the Siberian peoples - Vrtanesjan, G.S. (Archaeoastronomy and Ancient Technologies, 2017)
The paper explores the calendar vocabulary and ways of performing intercalations in the calendars of the Tungus, Samoyeds, Buryats, and Turkic-speaking peoples of Siberia of the XVIII-XX centuries AD. An analysis is made of the etymologies and semantics of terms that denote the inserting months for some Tungus-speaking peoples, Nenets, Yakuts and Buryats. The difference in insertion procedures for solons (equine Evenks), borrowed the name of the insertable month (anaga) from the Manchus, and other Tungus-speaking peoples is shown. In the Evens calendars, along with the phenological names of the months, the time control system for parts of the body (joints), there are no direct indications of the existence of an additional time insertion procedure.